Effectiveness of adjuvanted seasonal influenza vaccines (Inflexal V(®) and Fluad(®)) in preventing hospitalization for influenza and pneumonia in the elderly: A matched case-control study - Gasparini, Roberto (Landes Bioscience, 2013)
Annual vaccination is the main mean of preventing influenza in the elderly. In order to evaluate the effectiveness of the adjuvanted seasonal influenza vaccines available in Italy in preventing hospitalization for influenza and pneumonia, a matched case-control study was performed in elderly subjects during the 2010–2011 season in Genoa (Italy). Cases and controls were matched in a 1:1 ratio according to gender, age, socio-economic status and type of influenza vaccine. Vaccine effectiveness was calculated as IVE = [(1-OR)x100] and crude odds ratios were estimated through conditional logistic regression models. Adjusted odds ratios were estimated through multivariable logistic models. In the study area, influenza activity was moderate in the 2010–2011 season, with optimal matching between circulating viruses and vaccine strains. We recruited 187 case-control pairs; 46.5% of cases and 79.1% of controls had been vaccinated. The adjuvanted influenza vaccines (Fluad(®) considered together with Inflexal V(®)) were associated with a significant reduction in the risk of hospitalization, their effectiveness being 94.8% (CI 77.1–98.8). Adjusted vaccine effectiveness was 95.2% (CI 62.8–99.4) and 87.8 (CI 0.0–98.9) for Inflexal V(®) and Fluad(®), respectively. Both adjuvanted vaccines proved effective, although the results displayed statistical significance only for Inflexal V(®) (p = 0.004), while for Fluad(®) statistical significance was not reached (p = 0.09). Our study is the first to provide information on the effectiveness of Inflexal V(®) in terms of reducing hospitalizations for influenza or pneumonia in the elderly, and demonstrates that this vaccine yields a high degree of protection and that its use would generate considerable saving for the National Health Service.